2016
DOI: 10.1634/theoncologist.2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Cognitive Function in Older Adults With Early-Stage Breast Cancer After Adjuvant Treatment

Abstract: Background. The impact of chemotherapy on cognition among elderly patients has received little attention, although such patients are more prone to presenting with age-related cognitive deficits and/or cognitive decline during chemotherapy. The present study assessed the cognitive function in older adults treated for early-stage breast cancer (EBC). Patients and Methods. The participants were newly diagnosed EBC patients aged $65 years without previous systemic treatment or neurological or psychiatric disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(163 citation statements)
references
References 59 publications
6
155
1
1
Order By: Relevance
“…Minisini et al prospectively measured cognitive function in older patients with breast cancer who received no adjuvant treatment or were treated with chemotherapy with or without endocrine therapy and found that more patients in the chemotherapy group showed worsening memory skills, and more patients in the endocrine therapy and chemotherapy group experienced reduction in attention scores . Other studies have raised concerns about the short and long‐term impact of chemotherapy in older adults with breast cancer …”
Section: Aging Cognition and Cancermentioning
confidence: 99%
“…Minisini et al prospectively measured cognitive function in older patients with breast cancer who received no adjuvant treatment or were treated with chemotherapy with or without endocrine therapy and found that more patients in the chemotherapy group showed worsening memory skills, and more patients in the endocrine therapy and chemotherapy group experienced reduction in attention scores . Other studies have raised concerns about the short and long‐term impact of chemotherapy in older adults with breast cancer …”
Section: Aging Cognition and Cancermentioning
confidence: 99%
“…Based on previous published results-which overall showed there was no significant difference between patient groups receiving or not receiving chemotherapy in objective cognitive decline in any cognitive domain or in at least one domain [5]-cognitive changes before to after treatment are presented independently of received treatment (chemotherapy and/or radiotherapy) and were elaborated from a decline in at least one domain.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of sample characteristics and main previous results [5] is presented here to place the methods and results of the present study in context. Newly diagnosed women with EBC (n 5 119) aged more than 65 years and a sample of healthy controls (n 5 62) were included.…”
Section: Sample Characteristics: Data Previously Publishedmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are few data on the long‐term effects with regards to quality of life and cognition. Lange et al demonstrated that older patients frequently present a cognitive decline after adjuvant chemotherapy, particularly docetaxel . In addition, adjuvant chemotherapy affects quality of life considerably in older patients .…”
Section: Incidence Of Main Adverse Eventsmentioning
confidence: 99%